(untitled) (Sebha University Conference Proceedings, 2024)
In this study, the main aim was to correlate the barely straw (BS) content with mechanical (e.g. impact strength and Shore hardness) and physical (e.g. water absorption (WA)) properties of BS/polystyrene butadiene rubber (SBR) composites. BS/SBR composites were prepared with 10, 20, 30, and 40% BS content. All composites showed to have improved mechanical properties in comparison to neat SBR. The impact strength slightly increased with increasing BS content up to 30% and then decreased. Shore hardness also showed a slight increase with increasing the content of BS. As expected, increasing BS content resulted in an increase in WA. Most importantly, a robustand positive correlation was found between BS content and impact strength, Shore hardness, and WA properties. The correlation indices between BS content and impact strength, Shore hardness and WA were r2 = 0.711, r2 = 0.966 and r2 = 0.943, respectively. Therefore, straw could to used as alternative raw materials for conventional wood in reinforcement of polymer composites.